Comparison of Delay in Tuberculosis Diagnosis Between Migrants and Local Residents in an Eastern County of China: An Analysis of the Electronic Data Between 2015 and 2019 - Xiao, Wenhui; Chen, Bin; Huang, Dajiang; Chan, Olivia; Wei, Xiaolin; Zhou, Lin; Zou, Guanyang (Frontiers in Public Health, 2021)
Introduction China continues to rank among one of the countries with the highest tuberculosis (TB) cases burden globally. Migrants are a particularly at-risk subgroup for TB and pose a challenge for case management in contemporary China. Early diagnosis and treatment of TB patients is pivotal for effective TB control. This study investigates TB diagnosis delay of migrants as compared to residents, to provide evidence base for improved case detection and better management of migrant TB patients. Materials and Methods Data was collected from China’s Tuberculosis Information Management System (TBIMS, 2015-2019) in an eastern county of China. Total diagnostic delay, consisting of patient delay and health system delay, is defined as the interval between the onset of TB symptoms and confirmation of TB diagnosis in the designated TB hospital. The comparison of delay in TB diagnosis between migrants and residents was made using Mann-Whitney U Test and Chi-square test. The difference in delay curves between these two groups was examined using log-rank test. Results Of 2487 TB patients, 539 (22%) were migrants. Migrants tended to be younger, present less severe conditions, receive initial diagnosis at prefectural and above level hospital. Compared with local TB patients, migrant TB patients had longer median total diagnostic delay (30 vs. 9, P=0.000) and higher proportion of patients with this delay >28 days (52% vs. 13%, P=0.000). Similarly, migrant TB patients also had longer median patient delay (13 vs. 9, P=0.000) and higher proportion of patients with this delay >14 days (47% vs. 30%, P=0.000), longer median health system delay (9 vs. 0, P=0.000) and higher proportion of patients with this delay >14 days (42% vs. 0.5%, P=0.000) than local TB patients. The survival curves of delay showed that the longer the time interval was, the more likely the migrant TB patients was to be diagnosed (P<0.05). Conclusions Diagnosis is significantly delayed among migrant TB patients. Our study highlights the importance of early screening and diagnosis for TB especially among migrants, to improve access and ensure better management for all TB patients.